2016
DOI: 10.1128/aem.01612-16
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Populations Associated with Smokeless Tobacco Products

Abstract: There are an estimated 8 million users of smokeless tobacco products (STPs) in the United States, and yet limited data on microbial populations within these products exist. To better understand the potential microbiological risks associated with STP use, a study was conducted to provide a baseline microbiological profile of STPs. A total of 90 samples, representing 15 common STPs, were purchased in metropolitan areas in Little Rock, AR, and Washington, DC, in November 2012, March 2013, and July 2013. Bacterial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 33 publications
3
38
1
Order By: Relevance
“…These authors showed that bacteria from the families Staphylococcaceae , Aerococcaceae and Enterococcaceae were most abundant in moist snuff; bacteria from the families Bacillaceae , Staphylococcaceae and Lactobacillaceae were most abundant in dry snuff; and bacteria from the families Staphylococcaceae and Aerococcaceae were abundant in Toombak. Similarly, Han et al (2016) recently showed that bacteria from the genera Tetragenococcus , Carnobacterium , Lactobacillus , Geobacillus , Bacillus , and Staphylococcus were dominant in smokeless tobacco products tested using a 16S rRNA sequencing method. In addition, Han et al (2016) completed culture-based detection methods on the smokeless tobacco products and showed that the following species were most commonly isolated from the tested products: Bacillus pumilus, B. licheniformis, B. safensis and B. subtilis.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…These authors showed that bacteria from the families Staphylococcaceae , Aerococcaceae and Enterococcaceae were most abundant in moist snuff; bacteria from the families Bacillaceae , Staphylococcaceae and Lactobacillaceae were most abundant in dry snuff; and bacteria from the families Staphylococcaceae and Aerococcaceae were abundant in Toombak. Similarly, Han et al (2016) recently showed that bacteria from the genera Tetragenococcus , Carnobacterium , Lactobacillus , Geobacillus , Bacillus , and Staphylococcus were dominant in smokeless tobacco products tested using a 16S rRNA sequencing method. In addition, Han et al (2016) completed culture-based detection methods on the smokeless tobacco products and showed that the following species were most commonly isolated from the tested products: Bacillus pumilus, B. licheniformis, B. safensis and B. subtilis.…”
Section: Discussionmentioning
confidence: 89%
“…Similarly, Han et al (2016) recently showed that bacteria from the genera Tetragenococcus , Carnobacterium , Lactobacillus , Geobacillus , Bacillus , and Staphylococcus were dominant in smokeless tobacco products tested using a 16S rRNA sequencing method. In addition, Han et al (2016) completed culture-based detection methods on the smokeless tobacco products and showed that the following species were most commonly isolated from the tested products: Bacillus pumilus, B. licheniformis, B. safensis and B. subtilis. …”
Section: Discussionmentioning
confidence: 89%
“…Several recent studies using next-generation sequencing have characterized the bacterial communities in a variety of tobacco products, including smokeless tobacco (Han et al, 2016; Tyx et al, 2016; Smyth et al, 2017), cigarettes (Chopyk et al, 2017a, b) and little cigars (Chattopadhyay et al, 2019). Our group recently showed that cigarette tobacco was dominated by bacteria from the genera Pseudomonas , Pantoea , and Bacillus , many of which contain potentially pathogenic species – such as Pseudomonas putida —that cigarette smokers may be exposed to over time (Chopyk et al, 2017a, b).…”
Section: Introductionmentioning
confidence: 99%
“…A total of 22 SLT products available in the market were analysed for contamination using bacterial culture. The number of brands to be included was based on previous studies conducted on SLT products in countries other than India [18][19][20] . All products were found to be contaminated with bacteria.…”
Section: Discussionmentioning
confidence: 99%